2021
DOI: 10.1186/s12940-020-00685-9
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal metal mixtures and child blood pressure in the Rhea mother-child cohort in Greece

Abstract: Background Child blood pressure (BP) is predictive of future cardiovascular risk. Prenatal exposure to metals has been associated with higher BP in childhood, but most studies have evaluated elements individually and measured BP at a single time point. We investigated impacts of prenatal metal mixture exposures on longitudinal changes in BP during childhood and elevated BP at 11 years of age. Methods The current study included 176 mother-child pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 82 publications
0
33
1
Order By: Relevance
“…Howe et al also did not find an association of Se (measured in maternal urine samples in pregnancy) with child BP at 4, 6, or 11 y (Howe et al 2021). Different findings between these two studies with ours could possibly be due to the differences in the biomarkers used, time points at biomarker collection and outcome assessment, metal mixtures that the children were exposed to, and unmeasured susceptibility factors and confounders.…”
Section: Mn and Secontrasting
confidence: 65%
See 1 more Smart Citation
“…Howe et al also did not find an association of Se (measured in maternal urine samples in pregnancy) with child BP at 4, 6, or 11 y (Howe et al 2021). Different findings between these two studies with ours could possibly be due to the differences in the biomarkers used, time points at biomarker collection and outcome assessment, metal mixtures that the children were exposed to, and unmeasured susceptibility factors and confounders.…”
Section: Mn and Secontrasting
confidence: 65%
“…The authors also did not observe evidence of interactions of these metals on BP. More recently, Howe et al found in a Greek cohort a potential interaction of Pb and molybdenum on child BP at 11 years of age (Howe et al 2021).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, the actual correlation between annual HD sales and annual diagnosed HDLIs might be higher than our observation. Finally, we cannot rule out the possibility that annual changes in air pollution may affect the annual changes in the volume of lung injury, because previous studies reported that air pollution is associated with lung injuries such as IPF [ 33 , 34 ], interstitial lung disease [ 35 ], and pneumonia [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have certainly known for decades that nutritional status can affect the toxicity of some pollutants (Mahaffey and Vanderveen 1979). Other examples of interactions between trace elements and metals related to a variety of child health outcomes also are beginning to emerge (Howe et al 2020a(Howe et al , 2020b(Howe et al , 2021Liu et al 2018). However, in many of these cases, the results suggest that the positive association between the trace element and these outcomes may be attenuated at higher levels of the toxic metal.…”
mentioning
confidence: 99%